Development and psychometric properties of Iranian women childbirth experience questionnaire - Monirolsadate Hosseini Tabaghdehi; Afsaneh Keramat; Zohreh Shahhosseini; Sakineh Kolahdozan; Mahmood Moosazadeh; Zahra Motaghi (Wiley, 2021)
Abstract Aim This study aimed to develop and psychometrics a questionnaire for assessing childbirth experience in Iranian women. Design Cross‐sectional study. Methods This cross‐sectional study was done in women who experienced childbirth within the last 12 hr to 2 months from May to December 2018. Questionnaire items were extracted from a comprehensive review of the available studies and questionnaires on childbirth experiences and definitions implied by qualitative interviews. The designed questionnaire was validated in three stages: face, content and construct. Cronbach's alpha was used to determine the reliability of the instrument. Result Iranian women childbirth experience questionnaire contained seven factors with 52 items which were called professional support, husband's and other important support, baby, preparation, fear, positive perception and control were extracted. The Cronbach's alpha coefficient after factor analysis was 0.62-0.92 and for the whole instrument was 0.91. The findings showed that Iranian women childbirth experience questionnaire was valid and reliable.